2022
DOI: 10.1021/acsmaterialslett.2c00796
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Work Function of Ti3C2Tx MXene by Molecular Doping without Changing its Surface Functional Groups

Abstract: Owing to their impressive electronic/optoelectronic properties, MXenes have attracted significant attention among the 2D materials research community. Their work function (WF) tunability, in particular, has permitted efficient interfacial band alignment engineering in several device applications. However, like most of their properties, the WF of MXenes highly depends on their surface terminations, making it hard to individually modify the WF without compromising other fundamental properties, which hinders the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…The pure nanosheets exhibit a characteristic peak centered at 321 nm, corresponding to the inherent interband transition, in addition to a broad absorption band at 759 nm assigned to the transversal surface plasmon (SP) mode. 59 Upon diazonium functionalization, the peak position of the interband transition remained unaltered, while the SP band experienced a redshift of 17 nm to 776 nm. Recent studies have demonstrated that the peak position of the transversal SP mode is independent of the lateral sizes of nanosheets in the absorption measurements on Ti 3 C 2 T x dispersions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pure nanosheets exhibit a characteristic peak centered at 321 nm, corresponding to the inherent interband transition, in addition to a broad absorption band at 759 nm assigned to the transversal surface plasmon (SP) mode. 59 Upon diazonium functionalization, the peak position of the interband transition remained unaltered, while the SP band experienced a redshift of 17 nm to 776 nm. Recent studies have demonstrated that the peak position of the transversal SP mode is independent of the lateral sizes of nanosheets in the absorption measurements on Ti 3 C 2 T x dispersions.…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly because of the effective electron transfer from Ti 3 C 2 T x to the fullerene components, inducing electron depletion in the subsurface energy states of the former, where the interband transition takes place. 59 Fig. 6b compares the absorption spectra of some physically-blended samples, prepared by mixing Ti 3 C 2 T x nanosheets and benzaldehyde and/or fullerenes with roughly the same content as f-MXene, C 60 -MXene, and C 70 -MXene (according to the TGA results).…”
Section: Linear Optical Propertiesmentioning
confidence: 99%
“…[7] Although ─F, ─O, and ─OH are the most common terminations induced by synthesis, surface doping can be easily incorporated into MXenes' surface, further modifying MXenes' optical properties. [84] A direct bandgap is desirable for light-emitting properties since it does not involve the emission of phonons. Phonons interrupt MXenes' light emission by electron-phonon and phononphonon scattering.…”
Section: Surface Terminationsmentioning
confidence: 99%
“…Ohmic contact formation between graphene and various semiconductor channel materials in TFTs can also be challenging due to the limited tunability of the graphene work function (WF) . Besides graphene, two-dimensional (2D) transition metal carbides/nitrides, so-called MXenes, have recently emerged as potential conductive electrode materials. Since their first report in 2011, , MXenes have received considerable attention owing to their unique combination of superior hydrophilicity, metal-like conductivity, optical transparency, tunable WF, versatile surface chemistry, and upscalable solution-processability. , These characteristics make MXenes particularly appealing for large-volume applications such as large-area electronics (LAE).…”
Section: Introductionmentioning
confidence: 99%